GEODHA – crowdsourced mapping tools for community problems - Pratul, Venkatesh (Nanyang Technological University, 2024)
Project GEODHA is a startup venture and software tool that lets the public report locations of various community challenges – littering sites, delayed civil construction projects, electricity outages, dirty water, and more. The crowdsourced data is a useful tool where the data analysis and heatmaps generated can help guide and implement solutions effectively. In many countries with cities with significantly high population density a major hurdle in tackling community challenges is the sheer complexity, size, and dynamic nature of the challenge – with causes, intensity, frequency, etc. of problems significantly varying across neighborhoods and making the implementation of effective solutions challenging, without the need for significant time and resources to comprehensively research the challenges. Crowdsourcing the data from the members of the public is thus a useful approach where everyone contributes to data collection, tracking, and adequately representing challenges in their communities. While data collection is not the solution, it is the first step towards implementing a comprehensive and effective solution where data analysis on the data aggregated from everyone offers many insights. Heatmaps generated help identify vulnerable and high-risk communities, where solutions need to be prioritized, and help in identifying bottlenecks in solutions implemented. GEODHA focuses on empowering communities by making these advanced data analytics easily understandable by and more accessible to all members of the public, thereby providing them with the data to hold relevant authorities with jurisdiction more accountable, and overall raising awareness on issues and its extent in their communities. The primary focus of GEODHA was chosen to be towards tackling littering and open dumps (illegal waste dumping sites) with the platform constructed keeping scalability in mind to be able to track other issues at a future data. The project involved interviews and primary market research to validate the problem and solution, design of the user interface of the application that members of the public would use, the creation of a functional prototype version of this application, performing a live demo run to collect sample data, design of large and efficient systems for data collection, user privacy protection measures and some examples of the possible data analytics. The project and the completed steps are in preparation to launch and operate the start-up venture.